2005
DOI: 10.1093/molehr/gah129
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic microvesicular form of Fas ligand in human early placenta: switching the tissue immune privilege hypothesis from cellular to vesicular level

Abstract: The local immune privilege of the fetus is created by the placenta. Fas ligand (FasL) expression in trophoblast has been implied as one of the mechanisms of fetal tolerance. However, the expression of membranal FasL by trophoblast has failed to explain this role of FasL. Two objections can be raised: (1) there have been contradictions considering which trophoblast cells, syncytiotrophoblast (ST) or cytotrophoblast, express FasL; (2) in vivo and in vitro studies have shown that the membranal form of FasL evokes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
149
1
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(159 citation statements)
references
References 45 publications
6
149
1
3
Order By: Relevance
“…In a recent report (36), cytoplasmic microvesicular forms of FasL were demonstrated in syncytiotrophoblasts, and although not able to demonstrate release, these investigators postulated the release of these intracellular microvesicles in the form of exosomes. Their hypothesis was supported by the demonstration of secreted full-length, biologically active FasL in microvesicular form in first and third trimester pregnancies (21,37).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In a recent report (36), cytoplasmic microvesicular forms of FasL were demonstrated in syncytiotrophoblasts, and although not able to demonstrate release, these investigators postulated the release of these intracellular microvesicles in the form of exosomes. Their hypothesis was supported by the demonstration of secreted full-length, biologically active FasL in microvesicular form in first and third trimester pregnancies (21,37).…”
Section: Discussionmentioning
confidence: 94%
“…Investigations have implicated placenta-derived exosomes as a key component in establishing the placenta as an immune-privileged site (36,37). These past studies have not addressed qualitative, quantitative, or functional characteristics of placental exosomes in normal term pregnancies or in pregnancy complications.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, exosomes secreted from cancer cells or in malignant effusions possess Fas ligands and mediate apoptosis of T cells [44][45][46]. In addition, placenta-derived exosomes of pregnant women [47][48][49][50] and IL-10-treated dendritic cell-derived exosomes [51] have immunoregulating functions. Based on our observations, the exosomes derived from EBVtransformed B cells showed an immunoregulatory function in vitro, although it remains to be determined whether trace amounts of unknown factors included in our exosomal fractions exert their effect.…”
Section: Discussionmentioning
confidence: 99%
“…The placenta is not only a source of nourishment and pregnancy hormones but also actively produces and releases various immunomodulatory factors to prevent rejection of the fetal semiallograft by the innate and adaptive maternal immune system (5,6). In previous reports, we and other researchers have shown that human placenta releases bioactive Fas ligand (FasL) 3 by exosomes that could induce suppression of intracellular signaling and apoptosis of T cells (4,(7)(8)(9). Exosomes are 30-to 100-nm-sized microvesicles with a defined morphology and phenotype that are formed and released through the late endosomal compartment of a variety of cells (10), including syncytiotrophoblast (STB) of human placenta (2,8).…”
mentioning
confidence: 99%
“…In previous reports, we and other researchers have shown that human placenta releases bioactive Fas ligand (FasL) 3 by exosomes that could induce suppression of intracellular signaling and apoptosis of T cells (4,(7)(8)(9). Exosomes are 30-to 100-nm-sized microvesicles with a defined morphology and phenotype that are formed and released through the late endosomal compartment of a variety of cells (10), including syncytiotrophoblast (STB) of human placenta (2,8). Exosomes can carry membrane-bound and cytosolic proteins, mRNA, and bioactive lipids to target cells and also transfer infectious agents between cells.…”
mentioning
confidence: 99%